Modern Geomorphic Processes Along the Taquari River in the Pantanal: A Model for Development for a Humid Tropical Alluvial Fan - DOI 10.5216/bgg.v19i1.15306 - O.C, Souza; M.R, Araujo (Boletim Goiano de Geografia, 2011)
.